FAMILY RELATIONSHIPS OF WOMEN HAVE FIBROMYALGIA SYNDROME AND USING ECOMAP GENOGRAM (Fiep Bulletin - online, 2013)
Fibromyalgia syndrome is a rheumatic disease characterized by widespread pain in skeletal muscles, which in no specific treatment, the goal is pain relief and improved quality of life. FMS has a major impact on quality of life, affects the personal, physical, family, professional and social. The inter relationship and family fribromialgia is the key point of understanding of SFM, it is with the individual with SFM spends most of the time, then we need to understand this medium. Understanding the inter-family relationships of women who have FMS using the genogram and eco-map. The research was conducted with 9 women with FMS participants Assistance Program Interdisciplinar-Univali/Itajaí-SC, which were constructed genogram and eco-map for each participant, which seeks to evaluate the inter-family relationships. We find positives as the group Fibromyalgia UNIVALI, religion and the company of children, grandchildren and friends, and the relationship with psychologist profession. In negative points was the absence of parents, poor relationship with children, deaths of children, children with drugs, alcoholism, aggression and death. Conclusion: genogramming demonstrated to be appropriate for use in the study that encompasses the dynamics and structure of families. It is noteworthy that different from other interviews, the making of the genogram and eco-map should not follow a previously established order. Moreover, it is necessary that during the interview the researcher not only pay attention to the verbal and nonverbal expressions. From the analysis of the genogram and eco-map perceives that was split in results strong relationships and social factors (group Fibromyalgia Univali, spirituality, friends, children, grandchildren, psychologist and occupation) and negative toward the family relationship ( absence of parents, poor family relationships, drugs, alcohol and aggression).
Keywords: eco-map; genogram; fibromyalgia syndrome and family